2017
DOI: 10.1038/sc.2016.183
|View full text |Cite
|
Sign up to set email alerts
|

Identification of temporal genes involved in the mechanisms of spinal cord injury

Abstract: Several temporal genes, including TGFβ2, TGFβ3, ALDH2, ALDH3A2, ARG1 and NOS3, might be involved in SCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The statistically significant DEGs were acquired by utilizing the "DEseq" package (Wang et al, 2010), and set adjusted P-value (FDR) < 0.05 and |log2 (fold change (FC)) | > 1 as inclusion criteria. Then a hierarchical clustering analysis was performed using the "gplots" package (Ma et al, 2017) in R/Bioconductor software based on the expression level of DEGs in different groups, and colors represent different clustering information.…”
Section: Differential Expression Analysismentioning
confidence: 99%
“…The statistically significant DEGs were acquired by utilizing the "DEseq" package (Wang et al, 2010), and set adjusted P-value (FDR) < 0.05 and |log2 (fold change (FC)) | > 1 as inclusion criteria. Then a hierarchical clustering analysis was performed using the "gplots" package (Ma et al, 2017) in R/Bioconductor software based on the expression level of DEGs in different groups, and colors represent different clustering information.…”
Section: Differential Expression Analysismentioning
confidence: 99%
“…Transcriptional changes after SCI have been extensively studied in lean animals (21,31,37); therefore, in the present study, we used a clinically relevant rat model of spinal contusion injury coupled with diet-induced obesity to determine gene expression changes to the cord. Specifically, after either a thoracic spinal cord injury (tSCI) or sham laminectomy (sham), animals were allowed to recover on regular chow diet for 4 wk and then provided a high-fat diet (HFD) for an additional 8 wk sufficient to produce obesity.…”
mentioning
confidence: 99%
“…To demonstrate the effect of SynCAM3 deletion, we evaluated the relationship between SynCAM3 and gene expression in the injured cord. The heat map visually showed dynamic changes in the expression of all genes at 2, 4, 7, and 14 DPI ( Figure 1 C) [ 34 , 35 ]. It was confirmed that the most genetic changes occurred at seven DPI, when the expression of SynCAM3 was the lowest after SCI.…”
Section: Resultsmentioning
confidence: 99%